The Memory of Central European Emigration and Exile: A Comparative Interpretation of the Novels of Louis-Philippe Dalembert, Lenka Horňáková-Civade and Véronique Mougin - Střelec, Karel (Porównania, 2025)
The paper deals with the topic of refugees in three prose works by the following authors: Avant que les ombres s’effacent (Before the Shadows Dissipate) by the Haitian writer Louis-Philippe Dalembert, Où passe l’aiguille (Where the Needle Fits) by the French author Véronique Mougin and Symfonie o novém světě (Symphony of the New World) by the Czech writer Lenka Horňáková-Civade. The study aims at a comparative and transcultural analysis of the key attributes with which exile and traumatic departure from the dynamically changing Central Europe of the mid-20th century are associated. Further, attention is paid to representations of the trauma of wars and conflicts as well as geopolitical transformations in order to compare literary techniques and practices in the (re)mediation of cultural, national or ethnic identities and their memory. Finally, the paper deals with the construction of the image of the other, the alterity, the new exilic home through the individual perspectives of the protagonists of each novel.